Comparison of generational effect on proteins and metabolites in non-transgenic and transgenic soybean seeds through the insertion of the cp4-EPSPS gene assessed by omics-based platforms - de Campos, Bruna K.; Galazzi, Rodrigo M.; dos Santos, Bruna M. [UNESP]; Balbuena, Tiago S. [UNESP]; dos Santos, Fábio N.; Mokochinski, João B.; Eberlin, Marcos N.; Arruda, Marco A.Z. (Elsevier, 2020)
This work evaluates different generations of transgenic (cp4-EPSPS gene) and non-transgenic soybean plants through proteomics and metabolomics. For proteomics purpose, 24 differentially abundant protein spots were found through 2-D DIGE, being 4 belonging to transgenic plants. From this total, 19 were successfully identified, storage proteins as predominant class. Some identified proteins are involved in growing and cell division, and stress response, such as LEA and dehydrin. For metabolomics, 17 compounds were putatively annotated, mainly belonging to the secondary metabolism, such as flavonoids. From these analyzes, all generations and varieties of the soybean are prone to be differentiate by PLS-DA. According to our results, transgenic plants appear to be more stable than non-transgenic ones. In addition, the omics-based approaches allowed access some relations between those differential spot proteins and metabolites, mainly those storage proteins and flavonoid.
Keywords: Generational effect; Mass spectrometry; Metabolite; Protein; Soybean; Transgenic